Analisis Kinerja Inbound Logistik Susu Segar di Koperasi Peternak Sapi Bandung Utara (KPSBU) Lembang - A. D. Mulia; E. Taufik; A. Atabany (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2022)
North Bandung Cattle Ranching Cooperative (KPSBU) Lembang is a single primary business cooperative that acts as a distributor of fresh milk produced by cows owned by its member breeders. The distribution of fresh milk from farmers to cooperatives is a movement of material flow from suppliers to factories known as inbound logistics. This study was aimed to analyze the inbound logistics performance of fresh milk at KPSBU Lembang, its value added for the farmer, as well as the nutritional and microbiological quality. SCOR-AHP was used to analyse inbound logistics performance. The Hayami method was used to analyse value added of fresh milk for the farmer. Fresh milk quality indicators were total solid, protein, fat, pH, specific gravity and total plate count. Obtained data were analyzed descriptively. The results showed that fresh milk inbound logistics performance at KPSBU Lembang was 92.77% (above average). The added value obtained by breeders based on concentrate input amounted to Rp. 8.464 per cow with a value-added ratio of 73.83%. The quality of fresh milk during inbound logistics fulfilled national standard SNI 3141.1.2011.